Science and Technology of Thermal Barrier Coatings - Jung, Yeon-Gil (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
TBC materials in the hot components of a gas turbine are exposed to extremely harsh environments. Therefore, the evaluation of various environmental factors in applying new TBCs is essential. Understanding the mechanisms for degradation which occur in comprehensive environments plays an important role in preventing it and improving the lifetime performance. The development of novel coating techniques can also have a significant impact on lifetime performance as they can alter the microstructure of the coating and alter the various properties resulting from it. This Special Issue presents an original research paper that reports the development of novel TBCs, particularly the application of advanced deposition techniques and novel materials.